Pasteurella multocida bacteremia associated with contact with a domestic animal: Case report (2019)
Pasteurella species are known to be one of the most frequently isolated in oral microbiota of domestic andwild animals, because of that, they are associated with skin and soft tissues infections secondary to bites andscratches. Systemic infections are uncommon, but are associated with dissemination from localized infectionsand some risks factors related to immunosuppression. We report a case of Pasteurella multocida bacteremia in an88 years old patient, associated with food sharing with his dog; a bacteremia mechanism never described beforein the medical literature. © 2019, Sociedad Chilena de Infectologia. All rights reserved.